1996
DOI: 10.1146/annurev.arplant.47.1.127
|View full text |Cite
|
Sign up to set email alerts
|

The Functions and Regulation of Glutathione S-Transferases in Plants

Abstract: Glutathione S-transferases (GSTs) play roles in both normal cellular metabolism as well as in the detoxification of a wide variety of xenobiotic compounds, and they have been intensively studied with regard to herbicide detoxification in plants. A newly discovered plant GST subclass has been implicated in numerous stress responses, including those arising from pathogen attack, oxidative stress, and heavy-metal toxicity. In addition, plant GSTs play a role in the cellular response to auxins and during the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
851
0
74

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,257 publications
(946 citation statements)
references
References 154 publications
21
851
0
74
Order By: Relevance
“…Glutathione and its metabolic enzymes interact with plant growth regulators, which are regarded as vital in the scheme of plant establishment both under normal and stressful conditions. GST expression in plants is induced by phytohormones such as SA, ethylene, cytokinin, auxin, ABA (Marrs 1996), methyl jasmonate (Moons 2003), and brassinosteroids (Deng et al 2007). Chen et al (2012) demonstrated that GST overexpressed in Arabidopsis thaliana plants had a signaling role and it regulated plant development by maintaining GSH pools.…”
Section: Droughtmentioning
confidence: 99%
“…Glutathione and its metabolic enzymes interact with plant growth regulators, which are regarded as vital in the scheme of plant establishment both under normal and stressful conditions. GST expression in plants is induced by phytohormones such as SA, ethylene, cytokinin, auxin, ABA (Marrs 1996), methyl jasmonate (Moons 2003), and brassinosteroids (Deng et al 2007). Chen et al (2012) demonstrated that GST overexpressed in Arabidopsis thaliana plants had a signaling role and it regulated plant development by maintaining GSH pools.…”
Section: Droughtmentioning
confidence: 99%
“…3B), but the genes encoding enzymes involved in phytoalexin biosynthesis, such as VvSTS1, were not induced. GSTs are known to be induced by xenobiotics, such as toxins (Marrs, 1996), and may thus be important in the removal of toxins in grapevine cells by limiting the induction of oxidative stress. However, (À)-terremutin (1) induces cell death after 3 days by a signalling cascade that differs from a defence-related pathway leading to necrosis, but this pathway still needs to be elucidated.…”
Section: Phytotoxic Activitymentioning
confidence: 99%
“…Although these alkaloids are not known to occur in the Brassicaceae, at least one of these genes is expressed, suggesting a role in secondary metabolism which has yet to be elucidated. This same BAC also contains a tandem array of seven genes encoding glutathione S-transferase (GST), which has been implicated in numerous plant processes including stress and pathogen responses, xenobiotic tolerance and vacuolar sequestration 20 . In total, 13 GST genes have been found on chromosome 2, with 4 of the other genes occurring as tandem pairs.…”
Section: Gene Contentmentioning
confidence: 99%